1991
DOI: 10.1161/01.res.69.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Resonance. The missing phenomenon in hemodynamics.

Abstract: To simulate a short segment of the aorta, we studied wave propagation in an elastic tube with a side branch balloon. The small balloon simulated the organ (group of arterioles). Ligation of this side branch would reduce the moduli of the higher harmonics when the length of the side branch was appropriate. Electrical analogy of vessels was used to analyze this phenomenon. This simulation can explain the ligation results we found in rats. It may also clarify the discrepancies between the prediction of the Womers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 9 publications
6
63
0
Order By: Relevance
“…This suggests that the aorta and closely related organs may cause coupled oscillation or resonance. 24,36 In the presents study, we found that CAD and CABG surgery could change not only TPp but also normalized the power of individual harmonics. Our findings suggest that cardiovascular disease might redistribute the energy in the cardiovascular system such that high-frequency oscillations are reduced while low-frequency oscillations are increased and in addition, an increase in TPp.…”
Section: Normalized Powers Of Individual Harmonicssupporting
confidence: 52%
See 2 more Smart Citations
“…This suggests that the aorta and closely related organs may cause coupled oscillation or resonance. 24,36 In the presents study, we found that CAD and CABG surgery could change not only TPp but also normalized the power of individual harmonics. Our findings suggest that cardiovascular disease might redistribute the energy in the cardiovascular system such that high-frequency oscillations are reduced while low-frequency oscillations are increased and in addition, an increase in TPp.…”
Section: Normalized Powers Of Individual Harmonicssupporting
confidence: 52%
“…Our findings suggest that cardiovascular disease might redistribute the energy in the cardiovascular system such that high-frequency oscillations are reduced while low-frequency oscillations are increased and in addition, an increase in TPp. By using the resonance theory of Wang et al, 24 the changes in the power spectrum of the plethysmographic waveform observed in this study might be caused by changes in coupled oscillation, which was in turn caused by changes in the effective plasma flow to various organs supplied by the aorta. The pathological changes in the blood vessels because of CAD and CABG might play a role in changing the effective plasma flow.…”
Section: Normalized Powers Of Individual Harmonicsmentioning
confidence: 71%
See 1 more Smart Citation
“…The effect of the coefficient of wave reflection at the tube end and the wall material parameters on the fluid volume flow-rate and the tube wall displacement is investigated. It is shown that the volume flow-rate phase spectrum characteristics depend only slightly on the wall properties and can be used in clinical diagnostics for finding the reflection coefficient from pressure and flow-rate records.Keywords: pulse wave, viscoelastic tube, wave reflection.The propagation of pressure waves in liquid-filled compliant tubes has been intensely investigated in connection with the analysis of pulse waves in arteries [1][2][3][4][5]. The arterial vessels are multilayer tubes of viscoelastic orthotropic material and blood is a concentrated suspension of aggregating particles; therefore taking into account the fluid and wall rheology leads to fairly cumbersome mathematical models [6,7] that can be investigated only numerically.…”
mentioning
confidence: 99%
“…The propagation of pressure waves in liquid-filled compliant tubes has been intensely investigated in connection with the analysis of pulse waves in arteries [1][2][3][4][5]. The arterial vessels are multilayer tubes of viscoelastic orthotropic material and blood is a concentrated suspension of aggregating particles; therefore taking into account the fluid and wall rheology leads to fairly cumbersome mathematical models [6,7] that can be investigated only numerically.…”
mentioning
confidence: 99%